The Change Management of Human Resource Development in Terrorism Prevention: Study at BIN-BNPT-Densus 88 - Dedi Prasetyo; Made Wilantara (Universitas Darussalam Gontor, 2025)
The purpose of this study was to examine changes in human resource development management within three Indonesian security agencies: the State Intelligence Agency (BIN), the National Counterterrorism Agency (BNPT), and the Special Task Force 88 (Densus 88), in response to the increasingly complex threat of terrorism. The research method employed a qualitative approach with a case study design, involving in-depth interviews, participant observation, and document analysis. Key informants were officials and staff involved in human resource development at BIN, BNPT, and Densus 88. The results indicate that BIN focuses on technology-based intelligence competencies, BNPT develops socio-psychological skills for counter-radicalization, and Densus 88 prioritizes tactical-operational skills in field operations. Based on Kurt Lewin's model of change (unfreeze, change, refreeze), the processes differ. At BIN, the unfreeze phase was triggered by intelligence disruptions and increasing digital threats, which prompted a technological-analytical transformation, followed by a refreeze phase in an AI and big data culture. In the BNPT (National Counterterrorism Agency), the unfreeze phase emerged from the ineffectiveness of coercive prevention, leading to socio-psychological HRD with a soft approach to deradicalization and counternarratives. Meanwhile, Densus 88 addressed the demands of tactical complexity and the risks of public legitimacy, thus encouraging adaptive human resource change and producing professional, precision law enforcement. This study also offers new theoretical insights into the application of Kurt Lewin's Model in counterterrorism agencies such as the State Intelligence Agency (BIN), the BNPT, and Densus 88. Unlike commercial or administrative organizations, where change can stabilize into a permanent